2021
DOI: 10.23960/jat.v9i3.5304
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KAILAN (Brassica oleracea var. alboglabra) PADA PERTANAMAN KEDUA

Abstract: Ketersediaan unsur hara sangat diperlukan dalam budidaya tanaman kailan (Brassica oleraceae var. alboglabra), khususnya N yang dapat diperoleh dengan pemberian pupuk NPK.  Penelitian ini bertujuan untuk mengetahui pengaruh pemberian dosis pupuk NPK terhadap pertumbuhan dan hasil tanaman kailan dan mengetahui dosis terbaik pupuk NPK untuk pertumbuhan dan hasil tanaman kailan.Penelitian dilaksanakan pada Oktober─Desember 2018 di rumah kaca Gedung Hortikultura dan Laboratorium Lapang Terpadu, Fakultas Pertanian, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…In other plants, it was also found that NPK fertilizer treatment significantly affected the number of leaves, leaf area index, plant height, and the number of productive branches of eggplant plants [26]. Treatment of NPK fertilizer up to a dose of 6.0 grams per plant significantly increased the number of leaves, plant height, crown width, leaf length, fresh weight, and root length [27]. Application of NPK fertilizer can increase the number of leaves, plant height, and leaf width of bok choy [27]…”
Section: Number Of Spinach Leavesmentioning
confidence: 92%
See 1 more Smart Citation
“…In other plants, it was also found that NPK fertilizer treatment significantly affected the number of leaves, leaf area index, plant height, and the number of productive branches of eggplant plants [26]. Treatment of NPK fertilizer up to a dose of 6.0 grams per plant significantly increased the number of leaves, plant height, crown width, leaf length, fresh weight, and root length [27]. Application of NPK fertilizer can increase the number of leaves, plant height, and leaf width of bok choy [27]…”
Section: Number Of Spinach Leavesmentioning
confidence: 92%
“…Treatment of NPK fertilizer up to a dose of 6.0 grams per plant significantly increased the number of leaves, plant height, crown width, leaf length, fresh weight, and root length [27]. Application of NPK fertilizer can increase the number of leaves, plant height, and leaf width of bok choy [27]…”
Section: Number Of Spinach Leavesmentioning
confidence: 98%
“…Kailan's height increased significantly due to NPK fertilizer treatment, up to a dose of 6.0 g/plant. Each increase in one unit dose of NPK fertilizer will increase plant height by 0.39 cm [22].…”
Section: Stem Lengthmentioning
confidence: 99%
“…Selain itu perlakuan pupuk NPK juga dapat meningkatkan diameter batang (Wasis dan Fathia, 2010). Aplikasi rabuk NPK secara signifikan dapat meningkatkan tinggi tanaman kailan sampai dosis 6,0 g/tanaman (Fadila et al, 2021).…”
Section: Tinggi Batangunclassified